Augmented Fish Health Monitoring for Washington Department of Wildlife; Five-year Project Report, 1986-1991 Final Report. - Kerwin, John; Roberts, Steve; Oman, Leni; Bolding, Bruce (Washington (State). Department of Fish and Wildlife., 1992)
The Augmented Fish Health Monitoring Project was funded by the Bonneville Power Administration (BPA) with the mandate to collect fish health data on the anadromous fish stocks of the Columbia River Basin in a standardized manner. The Washington Department of Wildlife began the project in 1986. Cumulative data and a final summary for this project are presented in this document. Fish stocks were examined monthly for length, weight, and health status at all Washington Department of Wildlife Columbia River Basin hatcheries. Assays for specific fish pathogens were conducted on all stocks of broodfish and smolts in the study area. Pathogens of interest were replicating viral agents, erythrocytic inclusion body syndrome virus (EIBSV), and Renibacterium salmoninarum. Sea-run cutthroat (SCT) were also sampled midway through the rearing cycle for R. salmoninarum. Juvenile fish were examined for the presence of any pathogen. Assays for Myxobolus cerebralis were conducted on fish stocks in several locations along the Columbia River. An organosomatic index analysis was made on each stock of smolts at the Cowlitz and Wells hatcheries. Results of the organosomatic index analysis were consistent between the years at each facility. However, the fish reared at Cowlitz displayed tissue changes associated with ceratomyxosis while those reared at Wells had a more desirable color and quality. Cell culture assays for viral agents in broodfish were positive for infectious hematopoeitic necrosis virus (IHNV) in all stocks at the Cowlitz Hatchery four out of five years in the study. Other stations were less consistent over the years. Only the sea-run cutthroat stock spawned at Beaver Creek was negative for any virus. Infectious pancreatic necrosis virus (IPNV) was isolated from summer-run steelhead (SS) broodfish at Wells in 1989 and 1991 and at Yakima in 1991. Inclusions that are characteristic of EIBSV were found in red blood cells of brood fish from the Wells Hatchery in 1990 and 1991. Data collected on EIBSV during the first two years of the project cannot be compared with the later three years due to changes in laboratory protocol. Isolations of IHNV in smolts were made from Cowlitz and Skamania hatcheries and the Gobar Rearing Pond. Epizootics of IHN occurred at Lyons Ferry, Beaver Creek, Cowlitz and Skamania hatcheries during the project, EIBSV inclusions were identified in very low levels from smolts from Beaver Creek, Chelan, Cowlitz, Eastbank, and Ringold. Assays for R. salmoninarum on broodfish and smolts revealed very low levels of infection and the disease was not a problem. Enteric redmouth disease was not observed in the project area. Cytophaga psychrophila was a chronic problem in young fish at Vancouver, Beaver Creek and Cowlitz hatcheries. Ceratomyxa Shasta was the only reportable parasite observed in the fish within the study area and caused yearly outbreaks of ceratomyxosis at the Cowlitz Hatchery. Fish at the Beaver Creek Hatchery were treated for furunculosis three of the five years of the project. An ozone water treatment plant has been installed to minimize the disease. Flow and density indexes and feed conversion did not vary significantly at the hatcheries during this project. Egg mortality averaged 12.94% throughout the project with a range from 4.39% to 29.10%. The mean fry mortality during the project was 15.08% with a range of 2.01 to 37.43%. The overall mortality for early rearing was 20.43%. Prespawning broodstock mortality was recorded for SS and SCT and averaged 5.18% with a range from 0 to 38.8%. Fungal invasion was the primary cause of death in adult fish. Epizootics of furunculosis, ceratomyxosis, bacterial coldwater disease, and IHN occurred during the project. Fewer cases were reported in more recent years. The BPA augmented fish health project helped WDW identify problem areas in fish health while they were occurring. This knowledge allowed us to develop strategies for improved fish quality. Overall the project has been invaluable in assisting us in the improvement of the health of our fish.